Bioarchaeology and dietary reconstruction across late antiquity and the Middle Ages in Tuscany, Central Italy - Riccomi, Giulia (Archaeopress archaeology., 2021)
This title presents the results of the first multidisciplinary bioarchaeological analysis to reconstruct living conditions in Tuscany between Late Antiquity and the Middle Ages. This was done through the examination of stress markers, including adult stature, periosteal reaction, cranial porosities, and linear enamel hypoplasia, and through palaeodietary reconstruction in order to explore the effects of socio-cultural and environmental factors in a diachronic perspective. The shift from Classical to Medieval times has long left its mark on the European historical consciousness. Nevertheless, the impact of this transition on living conditions and dietary practices remains a subject of debate, with a prevailing perception of these 'Dark Ages' as an impoverished phase following the collapse of the Roman agrarian villa system, particularly in the Mediterranean area.